Wireless Ultrasound Video Transmission for Stroke Risk Assessment: Quality Metrics and System Design - Pattichis, Marios S.; Panayides, Andreas S.; Pattichis, Constantinos S.; Loizou, Christos P.; Pantzaris, Marios C. (My University, 2010)
In this paper we discuss the use of clinical quality criteria in the assessment and design of ultrasound video compression systems. Our goal is to design efficient systems that can be used to transmit quality ultrasound videos at the lowest possible bitrates. This led us to the development of a spatially- varying encoding scheme, where quantization levels are spatially varying as a function of the diagnostic significance of the video. Diagnostic Regions of Interest (ROIs) for carotid ultrasound medical video are defined, which are then used as input for Flexible Macroblock Ordering (FMO) slice encoding. Diagnostically relevant FMO slice encoding is attained by enabling variable quality slice encoding, tightly coupled by each region's diagnostic importance. Redundant Slices (RS) utilization increases compressed video's resilience over error prone transmission mediums. We present preliminary findings on three carotid ultrasound videos at CIF resolution, for packet loss rates up to 30%. Subjective quality evaluation incorporates a clinical rating system that provides for independent evaluations of the different parts of the video. Experimental results show that encoded videos attain enhanced diagnostic performance under noisy environments, while at the same time achieving significant bandwidth requirements reductions.
Keywords: Ultrasound video video compression systems; Carotid ultrasound; Diagnostic Regions of Interest